2018
DOI: 10.1177/1533033818790490
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED: Long Noncoding RNA LINC00472 Inhibits Proliferation and Promotes Apoptosis of Lung Adenocarcinoma Cells via Regulating miR-24-3p/DEDD

Abstract: Objective:We aimed to detect the role of LINC00472 via regulating miR-24-3p and death effector domain-containing DNA-binding protein in lung adenocarcinoma.Methods:Long noncoding RNA, microRNA, and messenger RNA levels were determined using reverse transcription quantitative polymerase chain reaction. The expression of death effector domain-containing DNA-binding protein was determined using Western blot assay. 3-(4,5-Dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide (MTT) assay and colony formation assay … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
20
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 16 publications
1
20
0
Order By: Relevance
“…Notably, decreased expression of LINC00261 indicated a better prognosis in TSCC. Our study found LINC00261 regulated the expression of ENPP4 and ENPP5, however, these two genes have not been Several existing studies indicate that LINC00472 plays an important role in inhibiting tumor development (Shen et al 2015;Su et al 2018;Ye et al 2018). Our study also showed the similar results that higher expression of LINC00472 was associated with better prognosis.…”
Section: Discussionsupporting
confidence: 77%
“…Notably, decreased expression of LINC00261 indicated a better prognosis in TSCC. Our study found LINC00261 regulated the expression of ENPP4 and ENPP5, however, these two genes have not been Several existing studies indicate that LINC00472 plays an important role in inhibiting tumor development (Shen et al 2015;Su et al 2018;Ye et al 2018). Our study also showed the similar results that higher expression of LINC00472 was associated with better prognosis.…”
Section: Discussionsupporting
confidence: 77%
“…Several existing studies indicate that LINC00472 plays an important role in inhibiting tumor development (Shen et al, 2015; Su et al, 2018; Ye et al, 2018). Our study also showed the similar results that higher expression of LINC00472 was associated with better prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…Thus far, most research on miR - 24 - 3p has focused on its function in cancer using in vitro model systems. For instance, up or downregulation of miR - 24 is important for regulation of the growth and/or apoptosis of various cancer types, including breast cancer [40], lung adenocarcinoma [41], hepatocellular carcinoma [42], and colon cancer [43]. In the present study, we investigated its function in neuronal differentiation.…”
Section: Discussionmentioning
confidence: 99%